Integration of Local Wisdom Sia Sawau Su'u Sawale in Strengthening Islamic Character Education - Abd Salam (Prodi PAI STIT Sunan Giri Bima, 2025)
Globalization bring challenge to identity and character generation young , so that educational model is needed contextual Islamic character . Wisdom local Sia Sawau Su'u Sawale in Bima culture is believed to contain values sublime that can integrated in coaching character , but studies that connect both of them Still limited . Research This use approach qualitative descriptive through studies literature with analyze books , articles scientific , documents culture and literature Islamic education . Data analyzed use technique analysis content For identify mark philosophical Sia Sawau Su'u Sawale , mapping its suitability with principle education Islamic character , as well as formulate pattern relevant integration​ for generation young . Research find four category mark main in Sia Sawau Su'u Sawale : moral, social , spiritual, and community values . Values the own point strong meeting​ with principle morals Karim like trust , adab, ukhuwah , and muhasabah . Analysis results show that mark the can integrated through habituation in family , curriculum school , practice culture society , and the use of digital media. Integration of wisdom local with education Islamic character enriches approach pedagogical at a time strengthen identity culture and religiosity generation young. Required study advanced based empirical For test implementation of the integrative model This in practice formal education.